Determinant Job Satisfication and Performance Employee: Analysis Competence, Training, Job Experince - Muhammad Thamrin AR; Euis Saribanon; Aisyah Rahmawati; Yuwono D Sucipto; Primadi Candra Susanto (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study is to review the existing results of the variables and see the results from the perspective of the author. To do this, the study will use a literature review of 30 international articles and provide an overview of the results and perspectives of the authors. The results of the study show that some variables have an influence on exposure, but not all variables are present in every paper or research result. This can be used as a reference for the variables in this paper.